FAKTOR-FAKTOR YANG MEMPENGARUHI PROFIT DISTRIBUTION MANAGEMENT ATAS SIMPANAN DEPOSAN PADA BANK SYARIAH DI INDONESIA PERIODE 2009-2012 - Lailatul Arafiah, 10.05.52.0035; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2014)
The purpose of this study was to analyze the factors that affect the upper deposits Profit Distribution Management depositors in Islamic banks in Indonesia. Independent variables used in this study is the Profit Distribution Management. The dependent variable used is the Capital Adequacy, Effectiveness of Third Party Funds, Risk Financing, Return on Assets, and Deposits proportion.This study used a sample of Islamic banks registered in Bank Indonesia with the first quarter 2009 to fourth quarter 2012. Data collected by purposive sampling method. The sample used was 5 banks, namely Bank Rakyat Indonesia Syariah, Bank Syariah Mandiri, Bank Mega Syariah, Bukopin Syariah and Bank Muamallat.The test results of the test statistic indicates that the variable Return on Assets positive effect on the Profit Distribution Management. Variable Risk Financing and Proportion of Third Party Funds negatively affect Profit Distribution Management. While the variable Capital Adequacy and Effectiveness of Third Party Fund has no effect on Profit Distribution Management.Keywords: Profit Distribution Management, Capital Adequacy, Effectiveness of Third Party Funds, Risk Financing, Return on Assets, Proportion of Third Party Funds